Copy number variation of FCGR3B gene among severe dengue patient in Malaysia / Umi Shakina Haridan - Haridan, Umi Shakina (2015)
Fc Gamma Receptor 3B (FcyRIIIB, encoded by the gene FCGR3B) plays a crucial role in immunity triggered by cellular effector and regulatory functions. Copy number variation (CNV) of this gene has been previously reported to affect susceptibility to several autoimmune diseases and chronic inflammatory conditions. However, it remains a challenge to accurately determine the copy number of this gene in different individuals. Thus this study aimed to establish the most robust CNV genotyping assay by comparing the accuracy and efficiency of (i) quantative PCR (qPCR), (ii) Sequenom Mass ARRAY, and (iii) Paralogue Ratio Test-Restriction Enzyme Digest Variant Ratio (PRT-REDVR). Subsequently the distribution of FCGR3B CNV among the dengue patients in Malaysia was characterized and its association with the severity of the disease was determined. A total of 237 samples were recruited from various study hospitals, of which 191 samples were included into further experiments. 120 were clinically diagnosed as severe dengue or warning sign, while 71 were dengue fever (DF). In the comparison of the three CNV genotyping assays, qPCR showed a considerably broader distribution of signal intensity compared to the other assays, potentially introducing error in estimation of copy number. Both Sequenom and PRTREDVR showed lesser systematic bias, and estimate copy number within the correct range, although PRT-REDVR appears to be more precise and accurate method when genotype FCGRSB. Collectively PRT-REDVR was considered to be most appropriate in the study of multiallelic CNV of FCGR3B. Multiple independent assays should be considered to accurately genotype the CNV of FCGR3B. In the second part of the study, 168 dengue samples (108 case, defined as dengue patients with signs of vascular leakage, and 60 control, defined as dengue patients without vascular leakage) and 52 of healthy samples genotyped with PRT-REDVR were included in the genetic association study. The analysis revealed statistical significance between CNV of FCGR3B of control, case and dengue sample against CNV of FCGR3B of healthy sample, respectively (p = 0.012, p = 0.007 and p = 0.012). On the other hand, there is no significance association shows between case and control (p = 0.301). However, a trend towards the low copy number (CN <2) in case was observed, hence postulating that lower copy number may be attributed with vascular leakage in dengue. Larger number of samples however, is needed to address this postulation.